2023
DOI: 10.1108/rmj-10-2022-0027
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic recordkeeping – the New Zealand experience

Abstract: Purpose The purpose of this paper is to review the recordkeeping response to the COVID-19 pandemic in New Zealand. It identifies how archival authorities supported potential changes in recordkeeping practice as a result of constraints brought about by the pandemic, in particular the shift to work-from-home as the dominant paradigm. Design/methodology/approach Analysis of guidance, standards and initiatives published online by New Zealand archival authorities in the early stages of the pandemic was undertaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Previous studies mainly focused on the impacts and applications of records for services, work efficiency, and organizational objectives, as indicated by Tracey et al, (2023); Farrell et al, (2023); Lawan & Henttonen (2023) ;Chandler, (2022). Huang et al, (2023); Haraldsdottir et al, (2023), on the other hand, focused on the application of certain methods and technologies on specific scenarios and during constraint and limitation (Wendelken, 2023). Studies determining the ambit and applying statutory law on recordkeeping are the least conducted.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies mainly focused on the impacts and applications of records for services, work efficiency, and organizational objectives, as indicated by Tracey et al, (2023); Farrell et al, (2023); Lawan & Henttonen (2023) ;Chandler, (2022). Huang et al, (2023); Haraldsdottir et al, (2023), on the other hand, focused on the application of certain methods and technologies on specific scenarios and during constraint and limitation (Wendelken, 2023). Studies determining the ambit and applying statutory law on recordkeeping are the least conducted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These adversaries may result in untoward consequences like costs, civil and criminal suits, loss of trust, and disruption to activities and operations (Kautto & Henttonen, 2020). Thus, well-designed recordkeeping procedures and observing legislative and regulatory frameworks protect organizations and individuals against unlawful acts, including violation of privacy and confidentiality (DeRenzo et al, 2020) and other risks (Wendelken, 2023).…”
Section: Records Management Outcomes-legal Compliancementioning
confidence: 99%
“…There are numerous studies on working from home in general, but very little research has been done on the impact of working from home that focuses specifically on the domain of recordkeeping. In a recent study, Wendelken (2023) analysed the recordkeeping response of archival authorities to the COVID pandemic in New Zealand. Her results showed that the guidance provided by these authorities was unlikely to have supported the physical change of work environment experienced by employees and the consequent rapid changes in organizational systems and processes required for sustained remote working.…”
Section: Introductionmentioning
confidence: 99%
“…These changes could result in organizational, social and cultural impacts. She suggests that recordkeeping practice could be "anticipated as a concurrent concern and one that could have far-reaching ramifications over time" (Wendelken, 2023).…”
Section: Introductionmentioning
confidence: 99%